The girl who drew butterflies : how Maria Merian's art changed science - Sidman, Joyce (Clarion Books, 2022)
Presents an illustrated biography of seventeenth-century German naturalist Maria Merian, who was one of the first scientists to document butterfly metamorphosis and is called the world's first ecologist. Features color photographs and illustrations, quotes, a butterfly glossary, poems by the author, historical information, a timeline, and a note describing the author's own experience raising butterflies.